STUDY ON THE RECOVERY OF 1-BUTYL-3-METHYLIMIDAZOLIUM-BASED IONIC LIQUIDS AS SOLVENT IN DESULFURIZATION PROCESS - IDAHAM, NURUL FASIHAH (2018)
Ionic liquids (ILs) have been recognized as alternative solvents applicable in synthesis, separation, compounds extraction, catalysis and electrochemistry. The discovery of ILs in desulfurization process attracted the attention of researchers since they can give better performance in sulfur compounds extraction in terms of capacity and selectivity.